Atividades investigativas, como estratégia para o ensino-aprendizagem em ciências: propostas e aprendizagens - SOUZA, Simony Suely Paes de (2007)
Leaving of the premise that "teaching it requires to know to learn and to know to construct (together with our pupils) the learnings that we search", I developed a proposal of investigation activities, for the teach-learning in Sciences. I stand out that to give differentiated lessons, nor always it would be or it is easy, therefore it has a content to be fulfilled and to be finished, beyond a very short time carrying through them. Thus, my dissertation is an inquiry of the qualitative type, that if configures as an researchaction, on the activities programmed at moments, with pupils of 7 series of the basic education of two schools of the particular net of education of the city of Belém (called here, School and School B), having as content programmarian the human body. In the school, emphasizing the digestive system, we had the following moments: the great snack; a video on the process of alimentary and mini-gincana digestion (test). Already in school B, with the content on the Locomotive System, the moments: hypothetical construction of the human body, from the contour of a model; the walked one until an Academy of Gynnastics of activities; lessons in square of the school, in set with the professor of Physical Ed.; e finally, the confection of a CD-ROM with all the subjects worked, during the school year. In both the schools, had the moment of the reading of didactic books. We conclude that learnings, from investigation activities, and that they take in account the experiences, the questionings and the contributions of the pupils, they are effective, independent of the subject who will be boarded and the Institution of Education (public or particular). However, we consider that this methodology of work will function if the professor: 1 - it will be made use to continue its studies and 2 - to share with its pupils the flavors and to know them, as well as the teachings and the learnings.